Assessing student readiness through artificial intelligence-based comics to enhance literacy and Indonesian local wisdom values - Sutrisno; Azis, Abdul; Laksana, Sigit Dwi; Karliani, Eli; Hidayah, Yayuk; Ambarita, Prini Desima Evawani; Sujana, I Putu Windu Mertha; Simatupang, Ernawati; Isnaini, Isnaini (Jurnal Civics: Media Kajian Kewarganegaraan, 2026)
This study evaluates the use of artificial intelligence (AI)-generated comics as an instructional medium for assessing students’ literacy skills and their understanding of Indonesian local wisdom values. In the context of increasing educational digitalisation, this research explores how AI-generated comics can be integrated into culturally oriented learning. The study employed a mixed-methods design involving 450 students from 15 schools across seven provinces in Indonesia. Data were collected through pre-tests and post-tests, student response questionnaires, in-depth interviews, and participatory observations. The findings show a significant improvement (p < 0.05) in students’ performance after using AI-generated comics, with average increases of 32% in literacy scores and 28% in students’ understanding of local wisdom. Qualitative analyses indicate that students responded positively to the interactive comic format, which provided personalised content aligned with their preferences and learning needs. Overall, the results demonstrate that AI-generated comics can serve as an effective instructional tool for integrating digital technology with culturally relevant learning materials, offering implications for curriculum development and instructional practices in Indonesia.